Optimization of circular hole patterns on crashworthiness of polyurethane foam-filled CFRP rectangular tubes - Harri Junaedi; Tabrej Khan; Walaa Abd-Elaziem; Tamer A. Sebaey; Khaled Akkad (Results in Engineering)
This study examines the impact of hole sizes, patterns, and polyurethane foam (PUF) filling on the crashworthiness of rectangular carbon fiber-reinforced polymer (CFRP) tubes used in crash box structures. While integrating holes for connections and sensors is common, it can compromise structural integrity, making it essential to understand their impact on energy absorption and load-bearing efficiency. Despite prior research on CFRP crashworthiness, the interaction between PUF insertion and hole patterns in rectangular tubes remains underexplored. This study addresses that gap by analyzing how these combined parameters affect specific energy absorption (SEA), crush force efficiency (CFE), and progressive failure modes. A quasi-static axial compression test was conducted to evaluate the specific energy absorption (SEA) and crush force efficiency (CFE). The Taguchi method was applied to analyze four factors: hole diameter, PUF filling, and the number of holes in the x- and y-directions. Taguchi analysis combined with Grey relation analysis was performed to optimize the multi-response outputs simultaneously. The mono-response Taguchi analysis indicates that hole diameter has the greatest influence on the SEA value; meanwhile, PUF-filling has the highest effect on the CFE value. Based on the Taguchi-Grey relational analysis, the optimal configuration consists of an 8 mm hole diameter, PUF filling, two holes in the x-direction, and one hole in the y-direction. This optimization was confirmed through testing, with results showing a SEA of 24 J/g and a CFE of 0.62, slightly lower in SEA and higher in CFE than the neat PUF-filled tubes (26 J/g and 0.57, respectively).